Measure and Integration - Kesavan, S. (New Delhi: Hindustan Book Agency, 2019)
This book deals with topics on the theory of measure and integration. It starts with discussion on the Riemann integral and points out certain shortcomings, which motivate the theory of measure and the Lebesgue integral. Most of the material in this book can be covered in a one-semester introductory course. An awareness of basic real analysis and elementary topological notions, with special emphasis on the topology of the n-dimensional Euclidean space, is the pre-requisite for this book. Each chapter is provided with a variety of exercises for the students. The book is targeted to students of graduate- and advanced-graduate-level courses on the theory of measure and integration.
Chapter 1. Measure -- Chapter 2. The Lebesgue measure -- Chapter 3. Measurable functions -- Chapter 4. Convergence -- Chapter 5. Integration -- Chapter 6. Differentiation -- Chapter 7. Change of variable -- Chapter 8. Product spaces -- Chapter 9. Signed measures -- Chapter 10. Lp spaces.
Keywords: Functional analysis; Measure theory; Measure and Integration; Functional Analysis